Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Belanja Modal Pada Kabupaten/Kota Di Sumatera Utara - Siti Aisyah Nasution; Putri Marina Valentin; Armey Sarumaha; Abigail Manurung; Munawarah Munawarah (Politeknik Ganesha Medan, 2023)
This study was conducted in districts/cities in North Sumatra province during 2018-2021. This study aims to examine and analyze the effects of economic growth, regional income, general pension funds and private pension funds on investment spending. The approaches used in this study are quantitative and descriptive. The population of this study was 33 counties/cities in North Sumatra using this technique, so the sample included 132 financial statements from 4 years of observations. As well as technical documentation collects data through the regional government director's balance sheet website. The analytical method in this study is multiple linear regression. Therefore, the results of this study are positive effects of economic growth, regional initial income, general allocation fund, special allocation fund, together or not, on capital expenditure in the region. areas. Counties/Cities in North Sumatra for the period 2018-2021. Figure F > F Table results obtained (7.316 > 2.50), significance value 0.000 < 0.005. From the partial test results, economic growth, regional initial income, general allocation, and special allocation funds have a significant impact on district/city spending. Capital expenditure in North Sumatra